Clinico-epidemiology, malacology and community awareness of Schistosoma mansoni in Haradenaba and Dertoramis kebeles in Bedeno district, eastern Ethiopia. (13th July 2018) - Mohammed, Jemal; Weldegebreal, Fitsum; Teklemariam, Zelalem; Mitiku, Habtamu
Background: Schistosoma mansoni is a major public health problem. Different studies reported unidentified sites in Ethiopia with variable prevalence and intensity, but there is no report from this study area. Objective: To assess the clinico-epidemiology, malacology, risk factors, and community awareness of S. mansoni in Haradenaba and Dertoramis kebeles in the Bedeno district, eastern Ethiopia. Methods: A cross-sectional study was conducted among 1011 study participants in 413 systematically selected households from Haradenaba and Dertoramis kebeles from 30 June 2016 to 30 July 2017. Data were collected by using pretested, structured questionnaires, clinical examinations, and stool examinations. Stool samples were processed by the Kato-Katz method and examined microscopically. Snails were collected by scooping from water contact points. Data were analyzed using SPSS, version 16 statistical software. Result: The overall prevalence of S. mansoni was 35.7%. Heavy-intensity infection was detected in 8.9% of the study participants. Results included: participants who were unaware about the possible source of infection (adjusted odds ratio: 2.95; 95% confidence interval: 1.25, 7.95), modes of transmission (adjusted odds ratio: 5.51; 95% confidence interval: 3.52, 12.51), prevention (adjusted odds ratio: 4.01; 95% confidence interval: 2.00, 8.75) about schistosomiasis/bilharziasis were more likely infected with S. mansoni than those who were aware. Participants who swim or bathe in the river were more likely infected with S. mansoni than those who do not (adjusted odds ratio: 6.41; 95% confidence interval: 3.15, 11.25). Biomphalaria pfeifferi snails were collected from all water bodies in Haradenaba and Dertoramis, but they did not shed schistosome cercaria in the laboratory. Conclusion: S. mansoni infection is found in high magnitude in these study areas, despite not being previously reported. A majority of the study participants had low awareness about the source of infection, mode of transmission, and prevention methods of schistosomiasis. Efforts should be made to improve community awareness about transmission and prevention of schistosomiasis.